Платон. Аристотель - Лосев Алексей Федорович (Жизнь замечательных людей, 2000)
Экземпляры: (20211022) / Инвентарный номер: 27765 / Цена: 55.00 / Сис.шифр: 87.3(0) / Авт.знак: Л79 / ГРНТИ: 02 / ББК: 87.3(0)